2015
DOI: 10.1002/ejlt.201400584
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the stability of chocolates through the incorporation of soft and hard StOSt‐rich fats

Abstract: The presented study investigates the functionality of hard and soft StOSt-rich fats in plain and hazelnut-based filled dark chocolates. Blends of cocoa butter (CB) with different StOSt-rich fats, namely Vietnamese mango fat (VMF), Indian mango fat (IMF), its stearin (IMFst) and olein fraction (IMFol) were selected for application in these chocolate products based on their phase and crystallisation behaviour. It was shown that a fat phase formulation with CB/VMF 70/30 and CB/IMFst 70/30 increased the heat resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Specific gravity is considered a purity criterion for fats and oils while FFA reflects the degree of rancidity. The FFA value of commercial cocoa butter ranges from 0.42% to 3.11% (Tran et al., ), which are values compatible with a high potential for the use of MSKF as an alternative to cocoa butter in chocolate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific gravity is considered a purity criterion for fats and oils while FFA reflects the degree of rancidity. The FFA value of commercial cocoa butter ranges from 0.42% to 3.11% (Tran et al., ), which are values compatible with a high potential for the use of MSKF as an alternative to cocoa butter in chocolate.…”
Section: Resultsmentioning
confidence: 99%
“…The lower hardness value of the CBSC is also likely to be due to eutectic effects of the binary fat mixtures (Tran et al., ). These authors observed that mango fat rich in StOSt (1,3‐distearoyl‐2‐oleoyl‐glycerol) compared to POP is associated with a pronounced hardening effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chocolate products can be kept at a constant temperature, either at a low, an intermediate or a high temperature. Tran et al stored composite chocolate products both at 20 and 23°C and stated that fat bloom development was about three times faster at 23°C. However, some studies use specific temperature cycling programs to monitor and/or promote the formation of fat bloom .…”
Section: Relationships Between Oil Migration and Fat Bloommentioning
confidence: 99%